REVIEW ARTICLE ON MORBIDITY PATTERN AND HYGIENIC PRACTICES IN SCHOOL CHILDREN . - Uzma eram (International Journal of Research Science and Management, 2017)
Surveys reported that malnutrition, infectious diseases, intestinal parasites,diseases of skin, eye and ear and dental caries are more prevalent in children.Lack of personal hygiene along with poor sanitation causes personto-person transmission of infection. Infection and malnutrition form a vicious circle and leads to retardation of children’s physical development. Repeated attacks of infections compromise children’s attendance and performance at school and not uncommonly, can result in death.Although studies have been conducted on health problems among school children in India there are still several localities for which epidemiological information is not available.Soap, water, and latrines are essential for proper hygiene practice in schools. Early identification of childhood illnesses through regular school health check-ups help prevent complications